Effect of Dietary Zinc and Niacin on Laying Hens Performance and Egg Quality - El-Husseiny, O.M.; Abd-Elsamee, M.O.; Omara, I.I.; Fouad, A.M. (International Journal of Poultry Science, 2008)
The experiment was designed to evaluate the effect of supplemented zinc (Zn) and niacin (Nia.) on laying hen performance, egg quality, nutrient digestabilities and relative economical efficiency (EEf) from 28-43 weeks of age. Bovans White Laying hens fed diets supplemented with four different levels of Zn (70,105,140 and 175 mg/kg diet) in combination with four different levels of Nia. (30,150,300,450 mg/kg diet) in a factorial arrangement design. The diets which contained on 70 mg Zn/kg and 30 mg Nia/kg considered as a control. The results indicated that supplemented Zn and Niacin (Nia.) increased the egg production significantly (p ≤ 0.05) compared with the control group. The best feed conversion ratio (FCR) was observed when diet supplemented with Zn and Nia. at 175 and 30 or 175 and 450 mg/kg, respectively. Egg weight (EW) did not improve by supplementing Zn and Nia. Supplemented Zn at 105 mg/kg recorded the best serum total immunoglobulin titres (STIT), While, supplemented Nia. at 300 mg/kg gave the best STIT. Supplemented Zn and Nia. had significant effect on egg shell thickness (EST), blood hemoglobin (BH) and nutrient digestabilities especially improving crude protein digestibility linearly parallel with dietary Zn levels increased. Supplemented Zn at level of 105 mg/kg with 30 mg Nia/kg or 175 mg Zn/kg with 30 or 450 mg Nia/kg gave the highest economical efficiency. Feeding laying hen on diet containing 105 mg Zn and 30 mg Nia/kg resulted in the best performance, egg quality and economical efficiency.